If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 6(x + -4) = 4(2 + -7x) Reorder the terms: -2x + 6(-4 + x) = 4(2 + -7x) -2x + (-4 * 6 + x * 6) = 4(2 + -7x) -2x + (-24 + 6x) = 4(2 + -7x) Reorder the terms: -24 + -2x + 6x = 4(2 + -7x) Combine like terms: -2x + 6x = 4x -24 + 4x = 4(2 + -7x) -24 + 4x = (2 * 4 + -7x * 4) -24 + 4x = (8 + -28x) Solving -24 + 4x = 8 + -28x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28x' to each side of the equation. -24 + 4x + 28x = 8 + -28x + 28x Combine like terms: 4x + 28x = 32x -24 + 32x = 8 + -28x + 28x Combine like terms: -28x + 28x = 0 -24 + 32x = 8 + 0 -24 + 32x = 8 Add '24' to each side of the equation. -24 + 24 + 32x = 8 + 24 Combine like terms: -24 + 24 = 0 0 + 32x = 8 + 24 32x = 8 + 24 Combine like terms: 8 + 24 = 32 32x = 32 Divide each side by '32'. x = 1 Simplifying x = 1
| (8+10x)*3= | | x-(5x+2)=-14 | | 21p^2+20p-25=0 | | 7m+10m=102 | | -8(2n+8)=-40+8n | | -2x-4x=-136 | | f^3-9f=0 | | (3x+5)(2x-3)=(x-1)(6x+5) | | 2(1-6x)+8=-38-4x | | -5o-9=4n+2 | | 5k-(2-1)k=13-7 | | -11.7x=46.8 | | 9a^2+21ac+10c^2= | | 10x-20x=2x-6 | | 5s-9=4s+2 | | x+4(x)=48 | | 8x-8(1+6x)= | | 6+2t-2=8t+20-4t | | -3(2b+1)+(7b-9)=0 | | 5x-y=180 | | 4(-8+3x)=4x+24 | | 3.9q-5.5-5.7q=-2.8q-3.4 | | 6n+13n=95 | | 19-ln(4-x)=0 | | 3b^2-17b-6= | | 3(8p-7)=-21+2p | | x+43=85 | | 7x-4(-3x-4)=-155 | | z+15-9=0 | | -2.5c+6.7=-13 | | 6x*6=8x-14 | | 6s^2-11s+3= |